Pengembangan Kompetensi Profesional Guru Dalam Meningkatkan Hasil Belajar Peserta Didik (Study Kasus UPTD SDN 3 Bojongkantong Kecamatan Langensari Kota Banjar) - Anna Suci Analis (Atmosfer: Jurnal Pendidikan, Bahasa, Sastra, Seni, Budaya, dan Sosial Humaniora, 2023)
This study aims to explain the importance of developing teacher professional competence as a key factor in improving student learning outcomes. In the context of education, the teacher's role is not only limited to conveying subject matter, but also involves the ability to plan, implement and evaluate the learning process. In an era of education that continues to develop, teachers must be able to face new challenges that arise, such as technological developments, curriculum changes, and the diverse needs of students. Therefore, teachers need to continue to develop their professional competence in order to meet the increasingly high demands and expectations from society, students, and the education system. The development of teacher professional competence includes various aspects, such as in-depth academic knowledge, effective teaching skills, ability to adapt to change, and a positive professional attitude. Teachers who have good professional competence are able to present a conducive learning environment, facilitate productive interactions between students, and provide constructive feedback. In this study, an analysis was conducted of various methods and strategies for developing teacher professional competence, such as training, supervision, mentoring, and collaboration between teachers. In addition, the factors that influence the success of teacher professional competence development are also discussed, including school leadership support, a conducive work environment, and teacher motivation in self-development. The results of the study show that the development of teacher professional competence has a significant effect on student learning outcomes. Teachers who have good professional competence are able to design interesting lessons, choose strategies that suit the needs of students, and provide effective feedback. This has a positive impact on the involvement of students in learning and increasing their academic achievement.